Female Pleasure and the Gender Politics of "Girliyapa". Issue 3 (1st December 2021) - Kumar Singh, Shailendra
Abstract: In this article, I examine the discursive portrayals of gendered experience and subject positions through Sarjita Jain's "Girliyapa, " an online entertainment channel (on YouTube) for female-oriented content in India. I demonstrate how the question of female pleasure that the channel repeatedly foregrounds by way of introducing relatively censored topics of discussion (such as girls buying condoms or articulating their orientation toward same-sex love) is inextricably intertwined with a gender politics that never turns a blind eye to the existing conventions, stereotypes, or structural inequalities that precipitate gender-based violence and discrimination throughout the country. The widespread prevalence of marital rape, color prejudice, and workplace sexism which, in turn, does not allow for a straightforward valorization of girl power is thus satirically interrogated by "Girliyapa."